(untitled) (ShodhVarta, 2023)
In the New Education Policy, several important aspects related to primary education in local/regional/mother tongues come to the fore, on the basis of which the true relevance of this education policy, its limitations and possibilities can be determined. In this policy, the structure of school education has been set as 5+3+3+4, under the child is given the option of studying three languages on the basis of trilingual mantra from the first day of education from the age of three. In this trilingual sutra for Hindi speaking region, Hindi, English and any language in the 8th Schedule or Sanskrit; While for non-Hindi speaking region mother tongue, English and local language have been included. In this policy, it is also clarified that the medium of education should be the mother tongue or the local language at least up to the fifth grade. The students who’s medium of education will be the mother tongue should have study science in their mother tongue and English as two languages from the eighth grade or earlier. When we try to understand this educational framework in a broader way, it appears on the surface as a model for acquiring education in the local/mother tongue. In the paper, an attempt has been made to highlight the real relevance of the new education policy for Indian languages.